2016
DOI: 10.3727/096368915x689767
|View full text |Cite
|
Sign up to set email alerts
|

Therapeutic Potential of Adipose-Derived Therapeutic Factor Concentrate for Treating Critical Limb Ischemia

Abstract: Transplantation of adipose-derived stem cells (ADSCs) is an emerging therapeutic option for addressing intractable diseases such as critical limb ischemia (CLI). Evidence suggests that therapeutic effects of ADSCs are primarily mediated through paracrine mechanisms rather than transdifferentiation. These secreted factors can be captured in conditioned medium (CM) and concentrated to prepare a therapeutic factor concentrate (TFC) composed of a cocktail of beneficial growth factors and cytokines that individuall… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
21
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 14 publications
(23 citation statements)
references
References 27 publications
1
21
1
Order By: Relevance
“…In our previous study using the rabbit model of critical limb ischemia, we demonstrated that ASC-CM can accelerate neovascularization and significantly improve ischemic tissue reperfusion 8 . A possible mechanism of revascularization was the promotion of angiogenesis by the growth factors and cytokines in the ASC-CM-treated group.…”
Section: Discussionmentioning
confidence: 92%
See 4 more Smart Citations
“…In our previous study using the rabbit model of critical limb ischemia, we demonstrated that ASC-CM can accelerate neovascularization and significantly improve ischemic tissue reperfusion 8 . A possible mechanism of revascularization was the promotion of angiogenesis by the growth factors and cytokines in the ASC-CM-treated group.…”
Section: Discussionmentioning
confidence: 92%
“…Adipose tissue was obtained from a single male patient (40 years of age, BMI 54 kg/m 2 ) undergoing elective lipoplasty. The tissue was processed for stromal vascular fraction (SVF) isolation using a Cytori Celution device as described previously 8 . Preparation and characterization of ASC-CM was performed as in the previous study 8 .…”
Section: Asc Isolation Asc-cm Preparation and Characteristicsmentioning
confidence: 99%
See 3 more Smart Citations